Influence of inter-parental conflict on adolescent delinquency via school connectedness: Is impulsivity a vulnerability or plasticity factor?. (October 2016) - Liu, Sha; Yu, Chengfu; Zhen, Shuangju; Zhang, Wei; Su, Ping; Xu, Yang
Abstract: This study examined the mediating effect of school connectedness on the relationship between inter-parental conflict and adolescent delinquency, and impulsivity's moderation of the conditional effect of school connectedness. In total, 1407 Chinese students (mean age = 12.74 years, SD  = 0.57) from 4 middle schools completed anonymous questionnaires regarding inter-parental conflict, impulsivity, school connectedness, and delinquency. Path analysis revealed school connectedness was a mediator in the relationship between inter-parental conflict and adolescent delinquency. Furthermore, impulsivity moderated the indirect effect of school connectedness in the relationship between inter-parental conflict and adolescent delinquency. A simple slope plot, together with a proportion affected (PA) index, indicated that impulsivity functioned more as a plasticity, rather than a vulnerability, factor in school connectedness. When school connectedness was low, high impulsivity was associated with more delinquent behaviors; however, when it was high, high impulsivity was associated with fewer delinquent behaviors.